Application of Steganography to Audio Files with Least Significant Bit (LSB) Process and Vigenere Cipher Encryption - Heri Santoso (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
Current technological developments, making the information very important, then the need arises in sending information that contains secrets. To solve this information security problem, the method that can be used is cryptography to encode messages using the Vigenere Cipher algorithm and steganography to hide messages using the Least Significant bit (LSB) method. This steganography application is able to insert text messages in files that have the format * .txt, * .docx, and * .pdf, but the size of the amount of text does not exceed the cover capacity of the audio file and can extract the text that has been inserted again. This application is also capable of encrypting and decrypting text files in * .txt, * .docx and * .pdf formats. Tests conducted on the audio size, audio that has a large bit rate will have a large capacity.